POTENSI LIMBAH PENEBANGAN DI HUTAN ALAM DAN FAKTOR YANG MEMPENGARUHINYA - Kedang, Paulus Nadun; Sari, Diah Rakhmah (JURNAL RIMBA LESTARI, 2022)
Timber harvesting does not only have to produce good quality logs, but the important thing is also to meet the quantity of wood for industrial needs. However, the process of harvesting wood, especially in logging activities in logging plots, cannot avoid the occurrence of logging waste. The purposes of this study were to determine the volume of logging waste, the volume of wood used, the percentage of waste in the logging plots in natural forest, and the factors that influence it. Primary data were taken by measuring the slope of the logging area, diameter and length of stump and stem waste in the logging plots on 85 samples in three plots, namely plots 2, 7 and 23 in 2020 Block area at PT Kemakmuran Berkah Timber. Meanwhile, secondary data consisted of tree species and the area (plot) of the study site. The results showed that the volume of stump waste in the felling plots is greater than the volume of stem waste, where the total waste stump is 46.99 m3 with an average waste volume per tree of 0.55 m3, while the total volume of stump waste is 30.2 m3 with an average volume of trunk waste per tree of 0.35 m3. The total volume of stump and stem waste is 77.55 m3 with an average waste volume per tree of 0.91 m3. The average volume of waste utilized per tree is 5.23 m3 and the average per hectare is 1.80 m3. Overall, the percentage of waste that occurred in the logging plots was 44.40%, with an average volume percentage of waste per tree of 0.52% and an average of 0.18% per hectare. The factors that influence the occurrence of logging waste at PT KBT are the diameter of the stump, the diameter of the stem waste, and the type of sinker wood.